Tapinarof and its structure-activity relationship for redox chemistry and phototoxicity on human skin keratinocytes - Zatloukalova, Martina; Hanyk, Jiri; Papouskova, Barbora; Kabelac, Martin; Vostalova, Jitka; Vacek, Jan (Free radical biology & medicine, 2024)
Tapinarof (3,5-dihydroxy-4-isopropylstilbene) is a therapeutic agent used in the treatment of psoriasis (VTAMA®). In this study, we examined the redox behaviour, (photo)stability, (photo)toxicity and (bio)transformation of tapinarof in the context of a structure-activity relationship study. Selected derivatives of the structurally related tapinarof were investigated, namely resveratrol, pterostilbene, pinosylvin and its methyl ether. Tapinarof undergoes electrochemical oxidation in a neutral aqueous medium at a potential of around +0.5 V (vs. Ag|AgCl|3M KCl). The anodic reaction of this substance is a proton-dependent irreversible and adsorption-driven process. The pKa value of tapinarof corresponds to 9.19 or 9.93, based on empirical and QM calculation approach, respectively. The oxidation potentials of tapinarof and its analogues correlate well with their HOMO (highest occupied molecular orbital) energy level. The ability to scavenge the DPPH radical decreased in the order trolox ≥ resveratrol > pterostilbene > tapinarof > pinosylvin ≫ pinosylvin methyl ether. It was also confirmed that tapinarof, being a moderate electron donor, is able to scavenge the ABTS radical and inhibit lipid peroxidation. The 4′-OH group plays a pivotal role in antioxidant action of stilbenols. During the stability studies, it was shown that tapinarof is subject to spontaneous degradation under aqueous conditions, and its degradation is accelerated at elevated temperatures and after exposure to UVA (315–399 nm) radiation. In aqueous media at pH 7.4, we observed an ∼50 % degradation of tapinarof after 48 h at laboratory temperature. The main UVA photodegradation processes include dihydroxylation and hydration. In conclusion, the phototoxic effect of tapinarof on a human keratinocytes cell line (HaCaT) was evaluated. Tapinarof exhibited a clear phototoxic effect, similar to phototoxic standard chlorpromazine. The IC50 values of the cytotoxicity and phototoxic effects of tapinarof correspond to 27.6 and 3.7 μM, respectively. The main HaCaT biotransformation products of tapinarof are sulfates and glucuronides. [Display omitted] •Tapinarof, also benvitimod, is redox active moderate electron-donor.•Structure-activity relationship study is presented here with resveratrol analogues.•Tapinarof undergoing irreversible adsorption-driven electrochemical anodic reaction.•The instability of tapinarof could be accelerated by higher temperature or UVA irradiation.•Tapinarof is phototoxic in uM concentration range after UVA irradiation of keratinocytes.